Sustainability Marketing, Entrepreneurial Orientation, and Café SME Performance: The Mediating Effects of Social Media - Budi Santoso; Nursaid Nursaid (Universitas Muhammadiyah Ponorogo, 2026)
This study investigates the strategic role of social media marketing in mediating the influence of sustainability marketing and entrepreneurial orientation on the performance of café SMEs in Jember Regency, East Java, Indonesia, a region recognized as a growing hub of the local creative economy with a strong presence of digitally savvy young consumers. Employing a predominantly quantitative approach, the study utilizes Partial Least Squares–Structural Equation Modeling (PLS-SEM) based on survey data collected from café consumers, complemented by in-depth interviews with café owners to provide interpretive triangulation. The research examines several structural relationships, including both direct and mediating effects among the key constructs. The findings indicate that sustainability marketing does not exert a strong direct influence on SME performance, whereas entrepreneurial orientation, reflected through proactiveness, innovativeness, and risk-taking behavior, plays a more prominent role in enhancing business performance. Furthermore, social media marketing is shown to function as an important mediating mechanism, strengthening the translation of sustainability initiatives and entrepreneurial practices into tangible business outcomes, such as improved sales performance, customer loyalty, and profitability. These results offer contextual empirical insights into the digital mediation processes shaping the transformation of local café SMEs and provide practical implications for business owners to optimize Instagram and TikTok content strategies, including green storytelling, influencer collaborations, and viral campaigns, in order to amplify the impact of sustainability efforts and entrepreneurial dynamics in achieving sustainable growth within a competitive market.